Penta-Helix Collaboration: Enhancing the Protection of Communal Intellectual Property in Bali - Desak Putu Dewi Kasih; Ni Ketut Supasti Dharmawan; Putu Aras Samsithawrati (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
This study aims to elaborate the policies related to the protection of communal intellectual property related to creative economy businesses in the tourism sector and to strengthen the protection of communal intellectual property by carrying out an inventory of traditional cultural expressions in Bali, especially in Gianyar Regency based on a penta-helix collaboration. This is socio-legal research with statutory, conceptual, economic, and technological approaches. The study indicated that communal intellectual property in the form of traditional cultural expressions has high economic value hence, it can be used to support the tourism creative economy business while still prioritizing the values ??that are believed by the community. Inventory must be carried out in accordance with Article 7 of Permenkumham 13/2007. The inventory has been carried out in Bali, although it has not been maximized. Inventory of traditional cultural expressions shall be carried out sustainably in the form of a penta-helix collaboration.